DIGITAL MARKETING BERBASIS MOBILE COMMERCE RUMAH UMKM DI PAGELARAN - Khotimah, Khusnul; Muslihudin, Muhamad; Yansahrita, Yansahrita (YHMM PUBLISHING, 2024)
The development of digital technology is currently very rapid, especially in the e-commerce sector. Digital marketing is promotional activities and market search through online digital media by utilizing various means such as social networks. The purpose of this study is to design a mobile commerce-based digital marketing platform for SMEs in Pagelaran by having adequate and competitive style promotional and marketing media, knowing the functions and features possessed by web-based media, especially for online promotion and marketing. The methods used in this study include data collection methods such as observation, interviews, and literature study and the system development method with the waterfall model. The results of this study are in the form of a mobile web-based MSME product promotion information system design that can help MSME business actors in developing efforts